THE ROLE OF PAI TEACHERS IN OVERCOMING STUDENTS' MORAL CRISIS IN THE SCHOOL ENVIRONMENT - Muhammad Ali Hamidi; Rizki Akmalia (Jurnal Bilqolam Pendidikan Islam, 2026)
The moral crisis among students has become one of the most pressing educational challenges in the modern era, particularly in the context of rapid technological development and social transformation in 2026. Schools are not only required to improve students’ academic achievement but also to strengthen character education and moral values. Islamic Religious Education (PAI) teachers play a strategic role in guiding students toward positive behavior and religious awareness. This study aims to analyze the role of PAI teachers in overcoming students’ moral crises in the school environment, identify the factors contributing to moral degradation, and examine the strategies implemented by teachers to strengthen students’ character. This research employed a qualitative descriptive approach using observation, interviews, and documentation techniques. Data were collected from PAI teachers, school principals, counseling teachers, students, and parents. The findings reveal that PAI teachers have significant roles as educators, role models, mentors, motivators, facilitators, and counselors. Religious habituation programs, moral guidance, digital literacy education, and collaboration between schools and families have proven effective in minimizing deviant behavior among students. However, several obstacles remain, including the influence of social media, weak parental supervision, peer pressure, and limited instructional hours for religious education. The study concludes that strengthening the role of PAI teachers through innovative learning methods, character-based education, and collaborative educational approaches is essential in addressing students’ moral crises in contemporary schools. This study contributes to the development of Islamic educational strategies that are relevant to the challenges of the digital era.